Investigation of the cascaded boost converter in a solar panel system - Cai, Wen Tian (2010)
In this final year project, the hardware prototype of the cascaded boost converter used in a solar panel system is constructed and investigated. The cascaded boost converter is controlled by the Proportional-Integral feedback controller by sensing the output voltage of the converter. By using the Pulse-Width-Modulation(PWM), the duty cycle of the converter is constantly changing to control the output voltage at a regulated level. The theoretical and the practical results will be compared and differences will be drawn.